Pengaruh Literasi Ekonomi Gaya Hidup dan Kontrol Diri Terhadap Perilaku Konsumtif Mahasiswa Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya - Khairulanam, Rafly Sucistiardhani; Surjanti, Jun (Jurnal Pendidikan Ekonomi (JUPE), 2024)
This study aims to determine the effect of economic literacy, lifestyle and self-control on the consumptive behavior of FEB UNESA students. The analysis technique used is multiple linear regression analysis using IBM SPSS 25 software with the number of samples in this study being 239 students. In this study obtained the results of economic literacy partially affect consumptive behavior, there is a partial influence of lifestyle on consumptive behavior, and self-control partially affects consumptive behavior. In addition, there is a simultaneous influence between conformity and family economic education on consumption behavior. The results of this study indicate that all independent variables in this model can be said to be appropriate and significant and have a contribution to the dependent variable. This study can provide an overview of the effect of economic literacy, lifestyle and self-control on the consumptive behavior of students of the Faculty of Economics and Business, Surabaya State University.